Dismantling Rape Culture The Peacebuilding Power of 'Me Too' - Nicholls, Tracey (Interdisciplinary Research in Gender, 2021)
"This book analyses rape culture through the lens of the 'me too' era. Drawing feminist theory into conversation with peace studies and improvisation theory, it advocates for peace- building opportunities to transform culture and for the improvisatory resources of 'culture- jamming' as a mechanism to dismantle rape culture. The book's key argument is that cultural attitudes and behaviours can be shifted through the introduction of disrupting narratives, so each chapter ends with a 'culture- jammed' re- telling of a traditional fairy tale. Chapter 1 traces an overlap of feminist theory and peace studies, arguing that rape culture is most fruitfully understood through the concept of 'structural violence.' Chapter 2 investigates the gender scripts that rape culture produces, considering a female counterpart to the concept of 'toxic masculinity': 'complicit femininity.' Chapter 3 offers analysis of non- consensual sex and a history of consent education, culminating in an argument that we need to move beyond consent to conceptualise a robust 'respectful mutuality.' Chapter 4 's history of sexual harassment in the workplace and the rise of #metoo argues that its global manifestations are a powerful peace- building initiative. Chapter 5 situates 'me too' within a culture- jamming history, using improvisation theory to show how this movement's potential can shape cultural reconstruction. This is a provocative and interventionist addition to feminist theory scholarship and is suitable for researchers and students in women's and gender studies, feminist theory, sociology and peace studies."